Pengaruh Manajemen Sumber Daya Manusia Dan Ancaman AI Terhadap Kesenjangan Keterampilan Dasar Karyawan Di PT SUCOFINDO (Jurnal Riset Manajemen dan Akuntansi, 2025)
The advancement of artificial intelligence (AI) has reshaped the workforce landscape, introducing new challenges in human resource management. This study aims to analyze the influence of human resource management (X1) and artificial intelligence threats (X2) on the basic skills gap (Y) of employees at PT SUCOFINDO. The research applies a quantitative method using multiple linear regression with 61 respondents selected through purposive sampling. The results show that both X1 and X2 simultaneously have a significant effect on Y (p = 0.000), but only X2 has a partial significant influence (p = 0.000; coefficient = 0.586), while X1 is not significant (p = 0.986). These findings indicate that perceived AI threats play a major role in widening the basic skills gap. On the other hand, current HR practices are ineffective in addressing the issue. The implication of this study emphasizes the need for data-driven HR strategies and adaptive training programs to reduce the skills gap and prepare employees for digital transformation.